Techniques of synergistic effect formation in marketing communications on the aesthetic medicine market - E. V. Bernikova; E. V. Tikhonova (Вестник университета)
The article analyses the experience of the Russian distribution company of the market of aesthetic medicine in implementing the communication strategy of a new educational product in a turbulent marketing environment. The paper formulates the principles of establishing profitable communication with core audiences, substantiates the choice of marketing communications instruments, as well as the techniques for their combination and the development of advertising material used for achieving synergistic effect from marketing and advertising activities. The authors notice a high value of Integrated marketing communications in the projects of launching new products to the market. The results of the study can be used by marketing specialists to form an effective communication system in small and medium-sized businesses that provides a commercial enterprise with a highly profitable result from advertising campaigns with limited deadlines and budgets.